2021
DOI: 10.1186/s13049-021-00910-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of emergency services for chemical incidents in Sweden - a multi-agency focus group study

Abstract: Background In chemical incidents, infrequent but potentially disastrous, the World Health Organization calls for inter-organizational coordination of actors involved. Multi-organizational studies of chemical response capacities are scarce. We aimed to describe chemical incident experiences and perceptions of Swedish fire and rescue services, emergency medical services, police services, and emergency dispatch services personnel. Methods Eight emerge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The category ‘The importance of ensuring the safety of citizens and personnel of emergency organizations’ emphasises the importance of ERC personnel’s situation awareness for their ability to give correct information and sound advice, because the chemical incident site may still be dangerous. Prior literature also states that it is important for ERC personnel to be able to assess risks, reassure and give the caller appropriate instructions and safety advice, as well as to gather and share information with the emergency organisations in order to prepare them—both tasks, when executed, will decrease the risks to all involved 16 24 25 29. This is important because it is relatively common that the personnel of the emergency organisations are injured during chemical incidents 30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The category ‘The importance of ensuring the safety of citizens and personnel of emergency organizations’ emphasises the importance of ERC personnel’s situation awareness for their ability to give correct information and sound advice, because the chemical incident site may still be dangerous. Prior literature also states that it is important for ERC personnel to be able to assess risks, reassure and give the caller appropriate instructions and safety advice, as well as to gather and share information with the emergency organisations in order to prepare them—both tasks, when executed, will decrease the risks to all involved 16 24 25 29. This is important because it is relatively common that the personnel of the emergency organisations are injured during chemical incidents 30.…”
Section: Discussionmentioning
confidence: 99%
“… 24 During chemical incidents this can be especially true if the incident type is not covered by the emergency dispatch index interview guide, or if the information about the incident is fragmented and several callers have to provide information for a full understanding of the situation, as reported in the study by Westman et al . 25 In situations having a clear emergency dispatch index, a swift response can be expected, thus dispatch indexes covering chemical incidents could be developed. As this result shows the ERC personnel’s gut feeling is central to picking up on cues that there has been a chemical incident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-incidents pose a considerable risk to the first responders, as the spread of chemical material may seriously affect their health. There is also a risk of secondary contamination (whereby a victim contaminates first responders) during the response (Westman et al, 2021;Clarke et al, 2008). Generally, all first responders receive training in managing major incidents through Prehospital Health-care Management (Rüter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results of some studies showed that, unfortunately, the level of preparedness for dealing with these events is low and the medical emergency is less prepared to manage these events [ 14 ]. Studies by Annelie Holgersson et al [ 15 ] and Westman Anton et al [ 16 ] stated that differences in viewpoints on terrorism preparation and response among emergency responders were demonstrating the significance of empowering inter-organizational insights on safety culture, risk perception, and management practices, as well as understanding of the other organizations’ institutional logics and main tasks, in order to achieve an effective, collaborative response to terrorism-induced incidents.…”
Section: Introductionmentioning
confidence: 99%